Holocaust in the Provinces of Lithuania in 1941: Massacre of Jews in Kaunas District - Bubnys, Arūnas (Genocidas ir rezistencija, 2002)
The article analyzes one holocaust aspect researched least up until now: genocide of Jews in the provinces. Kaunas district was selected as an example. The reason for this choice was that Kaunas was the administrative and political center of the Nazi occupied Lithuania. Namely, Nazi began implementing means of their occupational policy (also in regard to Jews) in Kaunas town and around it. That is why Kaunas district with minor exceptions can be considered the Jews' persecution and massacre model of all provinces of Lithuania. The article reveals major steps and elements of persecution of Jews in the provinces, and also presents statistical data on Jews massacred in the parishes of Kaunas district. Referring to the analysis of numerous archival material and historical literature such findings are made. The process of the Jews' persecution and extermination can be divided into two stages. During the first stage (end of June mid July, 1941) mostly political motives dominated. The Jews were mostly arrested, imprisoned, and shot for being former Communists, Communist youth, Soviet regime officers, and supporters. People of other nationalities (Lithuanians, Polish, Russians etc.) were also persecuted for the same reasons. During this stage, mostly terrorized were the males of Jewish nationality. Women, and especially children were not subject for mass arrests and fusillades. Persecution of Jews was mostly initiated by institutions of occupational Nazi authorities (military commandants, Nazi security police, SD operational and special squads). The second stage (end of July–August, 1941) can be considered the period of racial genocide (holocaust). The Jews were persecuted not for political reasons, but on the racial grounds, i.e. that they were Jews. Almost all Jews having lived in the provinces of Lithuania were mas- sacred during this period. According to the author's research, 4,211 (out of 4,363 Jews who lived there before the war) Jews were killed in Kaunas district. The peak of the massacre was in August and September of the year 1941. Still before the extermination of Jews in the provinces started, there were temporary ghettos and isolation camps established. This was a preparatory stage before the mass extermination. It started around the end of July 1941 in the provinces and lasted up until mid August of the same year. Before the ghettos and camps were finally liquidated, men and teenagers of Jewish origin were shot in most places. During the final stage of extermination of the province Jews all the rest were fusilladed: women, children, and the elders. The main perpetrators of these massacres were: the "flying squad" (Einsatzgruppen) lead by SS obersturmfürer Joachim Hamann, local (Lithuanian) self-defense squads, Lithuanian partisan squads, and the policemen from local precincts. By mid November 1941, actually, almost all Jews were massacred in the provinces. Only 3–5 percent Jews managed to survive or were saved by the local people.
Keywords: German occupation; Jews; Holocaust; Kaunas